Nano-Chitosan Particles in Anticancer Drug Delivery: An Up-to-Date Review - R. Kamath, Pooja; Sunil, Dhanya (Mini Reviews in Medicinal Chemistry, 2017)
Background: Cancer is one of the most awful lethal diseases all over the world and the success of its current chemotherapeutic treatment strategies is limited due to several associated drawbacks. The exploration of cancer cell physiology and its microenvironment has exposed the potential of various classes of nanocarriers to deliver anticancer chemotherapeutic agents at the tumor target site. These nanocarriers must evade the immune surveillance system and achieve target selectivity. Besides, they must gain access into the interior of cancerous cells, evade endosomal entrapment and discharge the drugs in a sustained manner. Chitosan, the second naturally abundant polysaccharide is a biocompatible, biodegradable and mucoadhesive cationic polymer which has been exploited extensively in the last few years in the effective delivery of anticancer chemotherapeutics to the target tumor cells. Therapeutic agent-loaded surface modified chitosan nanoparticles are established to be more stable, permeable and bioactive. Conclusion: This review will provide an up-to-date evidence-based background on recent pharmaceutical advancements in the transformation of chitosan nanoparticles for smart anticancer therapeutic drug delivery. Highlights: • Efforts to improve cancer chemotherapy by exploiting the intrinsic differences between normal and neoplastic cells to achieve maximum effective drug delivery to target cancer cells through bioengineered chitosan nano delivery vectors are discussed. • The easy manipulation of surface characteristics of chitosan based nanoparticles by various functionalization methods to achieve targeted drug delivery proves its potential to be an essential tool for the advancement of anticancer drug-delivery vectors.
Keywords: drug delivery